2021
DOI: 10.1371/journal.pone.0252968
|View full text |Cite
|
Sign up to set email alerts
|

Variance components of ratings of physician-patient communication: A generalizability theory analysis

Abstract: Background The ratings of physician-patient communication are an important indicator of the quality of health care delivery and provide guidance for many important decisions in the health care setting and in health research. But there is no gold standard to assess physician-patient communication. Thus, depending on the specific measurement condition, multiple sources of variance may contribute to the total score variance of ratings of physician-patient communication. This may systematically impair the validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The impact of simpler v. more complex SDMTs, and the impact of various types of SDM training on SDMT use and patients' decision making, is an ongoing area of active research. [38][39][40][41] As reported in other studies, PCPs do not have enough time to address preventive care services, 68 and as reported by Solberg et al, improving prevention care in busy primary care settings is difficult. 53,54,[64][65][66]69 Limitations Several factors limit the interpretation of these data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of simpler v. more complex SDMTs, and the impact of various types of SDM training on SDMT use and patients' decision making, is an ongoing area of active research. [38][39][40][41] As reported in other studies, PCPs do not have enough time to address preventive care services, 68 and as reported by Solberg et al, improving prevention care in busy primary care settings is difficult. 53,54,[64][65][66]69 Limitations Several factors limit the interpretation of these data.…”
Section: Discussionmentioning
confidence: 99%
“…SDMTs have received much attention over the past decade. 3842,57 Many studies of the use of SDMT in primary care settings have reported improved knowledge and decisional processes, but effects on clinical outcomes have been mixed. 42,58,59 Two studies on SDMTs for colorectal cancer screening showed no increase in screening, whereas 1 study reported a small effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antecedent factors influencing communication and developed communication climates may directly affect how treatment options are mutually selected in the SDM process [ 85 ]. Röttele et al observed that using generalizability theory to rate doctor-patient communication minimally indicates a doctor’s communication skills [ 86 ]. There are significant differences between doctors and patients regarding perceived SDM, effective and open communication, and satisfaction with communication.…”
Section: Discussionmentioning
confidence: 99%
“…Doctors tend to overrate the extent to which they apply SDM. Therefore, doctors should engage their patients more in SDM, even if they believe they have done so adequately [ 86 ].…”
Section: Discussionmentioning
confidence: 99%